(untitled) - Gitman, Lawrence J.; Lawrence J. Gitman; Michael D. Joehnk; Marilynn D. Hood (Mason, Ohio, 2005)
This text, now in its tenth edition, is clear and concise with shorter chapters that allow for flexible course organization without compromising coverage. Designed as a mid-level approach to personal financial planning, this text is written in a conversational style with many real-life examples. The life-cycle approach, practical applications, and decision-making focus are reinforced with expert advice, helpful tools, and real-life examples
Keywords: Finance; Personal